2020
DOI: 10.1016/j.ijid.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

A public-private model to scale up diabetes mellitus screening among people accessing tuberculosis diagnostics in Dhaka, Bangladesh

Abstract: Background: Data are scarce regarding the prevalence of diabetes mellitus (DM) among tuberculosis (TB) patients in Bangladesh. This study was undertaken to estimate the number needed to screen (NNS) to identify a case of DM among those with TB symptoms and those with confirmed TB disease, and to identify factors predicting treatment outcomes of TB patients with and without DM. Methods: Persons attending public-private model screening centres in urban Dhaka for the evaluation of TB were offered free blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Only 22% of patients in the private sector in 2020 had unknown or blank Diabetic status as compared to 76% of patients in the 2019 Private sector. A study by Paul et al on the public-private model to scale up DM screening while assessing TB showed 63% were cured with TB & DM 20. Such a design recruited a highly representative sample of urban TB dwellers, similar to our study (77%).…”
mentioning
confidence: 52%
“…Only 22% of patients in the private sector in 2020 had unknown or blank Diabetic status as compared to 76% of patients in the 2019 Private sector. A study by Paul et al on the public-private model to scale up DM screening while assessing TB showed 63% were cured with TB & DM 20. Such a design recruited a highly representative sample of urban TB dwellers, similar to our study (77%).…”
mentioning
confidence: 52%
“…For eight studies (27, 28, 33, 34, 48, 49, 57, 58, 60, 61, 70, 71, 84, 85, 87, 88), the research was reported across two publications each, which were merged and extracted as one study (Table 1 and Appendix 6). Most studies were from the WHO South-East Asia region (n=36, 65.4%) (30, 33, 36, 37, 4042, 45, 47, 48, 50, 51, 54–56, 59, 60, 62, 6467, 69, 7476, 7884, 86, 87, 89), followed by Eastern Mediterranean (n=7, 12.7%) (32, 43, 44, 46, 72, 73, 77), Western Pacific (n=6, 10.9%) (27, 31, 35, 52, 57, 70), African (n=4, 7.3%) (38, 39, 53, 68), and American (n=1, 1.8%) (63) regions. One study reported models from across three different countries and regions (29).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 29 studies reporting treatment success (27, 29, 31, 33, 35–37, 41, 4345, 51–54, 56, 57, 60, 62, 65, 66, 68, 73, 75, 77, 78, 81, 83, 89), 17 (60.7%) reported rates >=85%. Figure 2 plots the estimates from 21/28 studies (for which 95% CIs were reported or could be estimated), according to PPM model type.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study conducted in Riyadh, KSA and another one from Bangladesh endorsed that diabetic patients had pulmonary cavities more often than non-diabetics ( p -values = 0.02 and 0.001, respectively). 32 , 33 This could be ascribed to the immune dysfunction in diabetic patients induced by hyperglycemia. 34…”
Section: Discussionmentioning
confidence: 99%